(untitled) - Kundur, P. (New York, 2014)
Suitable for electric and utility engineers, power system stability and control, written by prabha kundur, comprises of numerous topics on voltage stability, with an aim to present the concepts in a clearer manner. It provides its readers with a generic introduction to the concept of electric power systems, stating its structure, design and operating criteria for stability references. It touches upon both mid-term as well as long-term voltage stability and discusses the problems of power system stability
Quá trình quá độ điện từ và ổn định hệ thống điện
Keywords: Electric power system stability.,Electric power systems,Ổn định hệ thống điện,Hệ thống điện năng; Control,Điều khiển